Autoimmune thyroid disorders—An update - Swain, Manorama (Springer India, 2005)
Background: Autoimmune thyroid disease (AITD), a common organ specific autoimmune disorder is seen mostly in women between 30–50 yrs of age. Thyroid autoimmunity can cause several forms of thyroiditis ranging from hypothyroidism (Hashimoto’s thyroiditis) to hyperthyroidism (Graves’Disease). Prevalence rate of autoimmune mediated hypothyroidism is about 0.8 per 100 and 95% among them are women. Graves’ disease is about one tenth as common as hypothyroidism and tends to occur more in younger individuals. Both these disorders share many immunologic features and the disease may progress from one state to other as the autoimmune process changes. Genetic, environmental and endogenous factors are responsible for initiation of thyroid autoimmunity. At present the only confirmed genetic factor lies in HLA complex (HLA DR-3) and the T cell regulatory gene (CTLA 4). A number of environmental factors like viral infection, smoking, stress & iodine intake are associated with the disease progression. The development of antibodies to thyroid peroxidase (TPO) thyroglobulin (TG) and Thyroid stimulating hormone receptor (TSH R) is the main hallmark of AITD. Circulating T Lymphocytes are increased in AITD and thyroid gland is infiltrated with CD4+ and CD8+ T Cells. Wide varieties of cytokines are produced by infiltrated immune cells, which mediate cytotoxicity leading to thyroid cell destruction. Circulating antibodies to TPO and TG are measured by immunofluorescense, hemagglutination, ELISA & RIA. TSHR antibodies of Graves’ disease can be measured in bioassays or indirectly in assays that detect antibody binding to the receptor.